A configuration of trade regimes in Eastern and Southern Africa region: Implication for deeper integration and WTO compatibility - Busieka, Wycliffe M (Department of Commercial Law, 2023)
This work has examined the implication the proliferation of identical econOITllC groupings portends for the east and southern Africa region. The thrust of the study here has been to interface and interrogate the incidence of the configuration of integration regimes in the east and southern Africa region. The work has investigated the question as to whether the proliferation of trade regimes has prepared a fertile ground for greater and deeper integration in the region. The thesis has also interrogated the proposition that such proliferation is the very antithesis of the desired goal to promote trade harmonization and reach out for deeper integration in the region. Importantly this work has ventured to query the confluence of identical trade regimes in view of the compatibility imperative as enshrined in the wro legal framework. We have examined the implication this configuration of integration regimes portends for the wro disciplines. This work conunenced with an extensive examination of current works on regional integration regimes in general and integration initiatives within the east and southern Africa region in particular. The interrogation exercise was premised on works, both economic surveys and legal treatises undertaken on the recently concluded EU-SA free trade agreement, the SADC Trade Protocol, the COMESA Treaty and the Cotonou Agreement. The actual texts of these instruments form the bulk of the sources. We note that without exceptlon, significant and to that extent costly restructuring programs will have to be undertaken by States in the east and southern Africa region in response to the disruptive EU-SA trade partnership. We have established that these integration regime scores well on the imperative of wro compatibility. We gather that the present wro structures are not malleable enough for the cash strapped sub-Saharan Africa trade regimes to reconfigure themselves in such a way as to deepen the integration agenda. We have urged for more flexibility in the wro framework on this score to augment integration processes currently crowding the regional landscape. Mataywa W Busieka - 10th July, 2003